2014
DOI: 10.1111/jcmm.12276
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed pro‐anthocyanidins ameliorates radiation‐induced lung injury

Abstract: Radiation-induced lung injury (RILI) is a potentially fatal and dose-limiting complication of thoracic radiotherapy. This study was to investigate the protective effects of grape seed pro-anthocyanidins (GSPs), an efficient antioxidant and anti-carcinogenic agent, on RILI. In our study, it was demonstrated that acute and late RILI was ameliorated after GSPs treatment possibly through suppressing TGF-β1/Smad3/Snail signalling pathway and modulating the levels of cytokines (interferon-γ, IL-4 and IL-13) derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…The fact that antioxidants were effective in ameliorating ionizing radiation-induced oxidative injuries has been demonstrated [ 12 , 13 ]. Previously, we have assessed that GSPs exhibited significant free radical scavenging ability in a cell-free Fenton system [ 4 ]. In the current study, we demonstrated that GSPs protected AHH-1 cells and mice from IR-induced injury, which may result from their radical scavenging effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that antioxidants were effective in ameliorating ionizing radiation-induced oxidative injuries has been demonstrated [ 12 , 13 ]. Previously, we have assessed that GSPs exhibited significant free radical scavenging ability in a cell-free Fenton system [ 4 ]. In the current study, we demonstrated that GSPs protected AHH-1 cells and mice from IR-induced injury, which may result from their radical scavenging effect.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have demonstrated that grape seed proanthocyanidins (GSPs) could effectively scavenge hydroxyl radical (•OH) in a dose-dependent manner [ 4 ]. In the current study, we investigated whether GSPs exerted radioprotective effect in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…There were two waves of increase in IFN-γ (same trend as for TGF-β1). IL-4 and IL-13 levels of mRNA in the lungs remained lower in the early time points, but stepped up progressively over 4 w. Huang et al [ 167 ] IL-4, IFN-γ, IL-12 C57Bl/6 Thorax 60 Co/20 Gy 1, 3 and 6 mo Invitrogen Bioplex BAFL The fibrotic cytokine IL-4 level in BALF from mice in the irradiation group increased significantly, the IL-12 level in BALF increased 1 mo after irradiation, and the IFN-γ level in BALF decreased significantly at intervals 3 and 6 mo. Xu et al [ 168 ] TNF-α, IL-17A, TGF-β1, IL-6 C57Bl/6 Thorax X-ray/15 Gy 1, 4, 8 and 16 w ELISA BALF The levels of TNF-α, IL-6 and TGF-β1 were significantly higher after irradiation at the 4 w time point; IL-17A reached a maximal concentration at 4 w, then slightly decreased.…”
Section: Cytokine Responses To Radiationmentioning
confidence: 99%
“…Lungs of mice received irradiation at a total dose of 20 Gy and a dose rate of 1 Gy/min. The irradiation source was 60 Co from the radiation center (Faculty of Naval Medicine, Second Military Medical University, China) [21, 22]. …”
Section: Methodsmentioning
confidence: 99%